(untitled) (Fiep Bulletin - online, 2014)
Tice is evidence based on an approach that involves the definition of a problem, the search and a critical evaluation of the evidence available, the implementation of evidence in practice and the evaluation of results. The implementation of this practice in nursing enables the improvement of the quality of care provided to clients and their families, since the trial intensifies the clinical nurse. For both, the nurses find strategies that enable their training in the development and use of research in practice. This is a systematic review, which were analyzed 05 publications, in order to identify the best curative / coverage given to the bearers of the venous leg ulcers. The data were collected through electronic searching electronic data bases of the Virtual Health Library (VHL) platforms in the Cochrane Library, LILACS, MEDLINE, BDENF and SCIELO and portal TESES.USP, using the descriptors: and venous ulcer healing. Located a total of 38 publications. After reading and analysis, considering the criteria for selection, were considered only 05 publications (02 systematic reviews, 01 memorandum of systematic review and 02 trials), the level of classified evidence II, according to the classification of the Agency for Healthcare Research and Quality (AHRQ) of the United States of America. The evidence sought in the literature showed that there is, currently, a specific type of healing that is better to be used by holders of the venous leg ulcers. Regardless of the type of remedial / cover to be applied in the venous ulcer, he has to be always associated with a therapy compressive.